A NEW GEOCHEMICAL MODEL FOR THE EARTH'S MANTLE INFERRED FROM 146SM-142ND SYSTEMATICS - Boyet M.; Carlson R.W. (My University, 2006)
New measurements of 142Nd/144Nd in kimberlites, carbonatites, komatiites, ocean island basalts from Pitcairn, and mid-ocean ridge basalts from the Pacific and Indian Oceans show no deviation from the terrestrial Nd standard within an external reproducibility of 8 ppm. Measurements of mafic rocks from Isua Greenland confirm previous discoveries of an excess of between 0 and 17 ppm in the 142Nd/144Nd of these rocks. Since the terrestrial Nd standard has a 142Nd/144Nd approximately 20 ppm higher than measured in chondrites and eucrites, all terrestrial rocks so far analyzed have superchondritic 142Nd/144Nd. This requires either that the bulk silicate earth has a superchondritic Sm/Nd ratio or that the Earth experienced a global differentiation event within a couple of hundred million years of planet formation that created complementary incompatible element enriched and depleted mantle reservoirs. If that portion of the mantle involved in the production of continental crust was originally characterized by incompatible element depletion (i.e. high Sm/Nd) rather than chondritic relative abundances of refractory lithophile elements, as is commonly assumed, the mass of mantle affected by continent formation may constitute as much as 80% or more of the mantle. The abundances of K, U and Th in this early-formed depleted mantle are 60-70% of those calculated for a "chondritic" mantle, which removes the inference that half of the 40Ar produced over Earth history must still reside in the mantle and explains why the mantle component characterized by high 3He/4He has superchondritic Nd and Hf isotopic composition. If these concentrations characterize the whole mantle, this implies a bulk-earth Urey ratio of ~ 0.3 and hence that much of the heat escaping the Earth's interior is primordial and not the result of radioactive decay over Earth history. If the bulk silicate earth is presumed to have chondritic abundances of refractory lithophile elements, there must be an incompatible element enriched reservoir buried deep enough in to mantle to preclude its involvement in mantle convection and its contribution to surface volcanism because no terrestrial rock with 142Nd/144Nd less than chondritic has been identified. © 2006 Elsevier B.V. All rights reserved.
Keywords: 142ND ANOMALY; EARLY EARTH DIFFERENTIATION; MANTLE COMPOSITION; RADIOGENIC ISOTOPE TRACERS; TIMS